Comparing The Tear Resistance Of PVC Sheets With Dioctyl Phthalate (DOP) And Epoxydized Soybean Oil (ESBO) Plasticizers - Prantasi Harmi Tjahjanti; Riki Nanda Setyo; Edi Widodo; Annisa Syakina (Ann Publisher, 2026)
Background. One of the PVC (Polyvinyl Chloride) products is a raincoat whose manufacture has been mixed with a DOP (Dioctyl Phthalate) plasticizer. The use of DOP in PVC since 1982 has been indicated as a chemical harmful to human health, especially causing gene mutations in the chromosomes of female eggs and infertility in men, as well as interfering with health. In addition, DOP is quite expensive. Aims. The purpose of the study is to replace DOP with the Epoxidized Soybean Oil (ESBO) plasticizer, which is non-carcinogenic, non-toxic, recyclable, and biodegradable. Methods. The PVC sheet products are tear-resistant and tested using the Elmendorf method. The mixing observed was analyzed using Fourier Transform Infrared (FTIR) spectroscopy. Result. The results using 100% ESBO meet the standard, even though the tear strength is still lower than with 100% DOP. Conclusion. FTIR analysis shows that a mixture of DOP and ESBO with a 50:50 ratio shows that other ingredients appear that do not interfere with the mixing process as a whole.